Differential CD4(+) T-cell responses of allergic and non-allergic subjects to the immunodominant epitope region of the horse major allergen Equ c 1 - Kailaanmäki, Anssi (Blackwell Science Inc, 2014)
The responses of allergen-specific CD4(+) T cells of allergic and healthy individuals are still incompletely understood. Our objective was to investigate the functional and phenotypic properties of CD4(+) T cells of horse-allergic and healthy subjects specific to the immunodominant epitope region of the major horse allergen Equ c 1. Specific T-cell lines (TCLs) and clones were generated from peripheral blood mononuclear cells with Equ c 1(143–160), the peptide containing the immunodominant epitope region of Equ c 1. The frequency, proliferative response, cytokine production and HLA restriction of the cells were examined. The frequency of Equ c 1-specific CD4(+) T cells was low (approximately 1 per 10(6) CD4(+) T cells) in both allergic and non-allergic subjects. The cells of allergic subjects had a stronger proliferative capacity than those of non-allergic subjects, and they predominantly emerged from the memory T-cell pool and expressed the T helper type 2 cytokine profile, whereas the cells of non-allergic subjects emerged from the naive T-cell pool and produced low levels of interferon-γ and interleukin-10. T-cell response to Equ c 1(143–160) was restricted by several common HLA class II molecules from both DQ and DR loci. As the phenotypic and functional properties of Equ c 1-specific CD4(+) T cells differ between allergic and non-allergic subjects, allergen-specific T cells appear to be tightly implicated in the development of diseased or healthy outcome. Restriction of the specific CD4(+) T-cell response by multiple HLA alleles suggests that Equ c 1(143–160) is a promising candidate for peptide-based immunotherapy.